2013
DOI: 10.1371/journal.pone.0068149
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Aqueous Concentrations of Cytokines in Macular Edema Secondary to Branch and Central Retinal Vein Occlusion

Abstract: PurposeThis study investigates the differential aqueous concentrations of interleukin 6, 8, 1β (IL-6, IL-8, IL-1β, respectively), serum amyloid A (SAA), transforming growth factor (TGF)-β, basic fibroblast growth factor (bFGF), and vascular endothelial growth factor (VEGF) in eyes with macular edema as a result of a branch retinal vein occlusion (BRVO) or central retinal vein occlusion (CRVO).Principal FindingsSignificantly higher concentrations of IL-6, IL-8, IL-1β, TGF-β, bFGF, SAA, and VEGF were found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 32 publications
1
33
0
4
Order By: Relevance
“…Анало-гичные изменения в стекловидном теле и влаге передней камеры также были описаны в ранее проводимых исследованиях [10,13,19,20,28].…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Анало-гичные изменения в стекловидном теле и влаге передней камеры также были описаны в ранее проводимых исследованиях [10,13,19,20,28].…”
Section: Discussionunclassified
“…Учитывая, что IL-6 -много-функциональный провоспалительный цитокин, повышение его концентрации при окклюзии вен сетчатки подтверждает его значение в иммуно-патогенезе данного заболевания, что также было отмечено некоторыми авторами [10,13].…”
Section: таблица 2 концентрация цитокинов в слезной жидкости на фонеunclassified
See 2 more Smart Citations
“…High levels of VEGF have been found in the aqueous and vitreous from subjects with DR (Endo et al 2000), neovascular age-related macular degeneration (AMD) (Jonas et al 2012;Miao et al 2012;Muether et al 2013), retinal vein occlusion (RVO) (Feng et al 2013) and retinopathy of prematurity (ROP) (Velez-Montoya et al 2010). It has also been shown that IOP level as well as success rates of surgical intervention in NVG subjects were associated with the intraocular level of VEGF ).…”
Section: Discussionmentioning
confidence: 99%